2014
DOI: 10.5430/cns.v2n2p123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heart disease knowledge and risk factors among first-generation Filipino Americans residing in Southern Nevada: A cross-sectional survey

Abstract: Objective: Filipino Americans are the second largest Asian subgroup in the United States and heart disease is their leading cause of death. Despite this, they remain an invisible minority and experience health disparities in cardiovascular health. Prior to implementing and designing health promotion programs, it is important to assess their level of knowledge about heart disease and to identify their risk factors. Purpose: We examined the baseline knowledge of heart disease among first-generation Filipino Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
6
11
0
4
Order By: Relevance
“…Socio demographic findings of this study revealed that 38.5% of the respondents were of age group 40-46 years and mean age of the respondents was 49.78 years which is similar to the study conducted in Southern Nevada which showed majority of the study subjects of age group 42-49 years with the mean age of 50.8 years (Angosta & Speck, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Socio demographic findings of this study revealed that 38.5% of the respondents were of age group 40-46 years and mean age of the respondents was 49.78 years which is similar to the study conducted in Southern Nevada which showed majority of the study subjects of age group 42-49 years with the mean age of 50.8 years (Angosta & Speck, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…The obtained results indicated that the knowledge of 57.51% of the study participants was at a good level. In a recent study, the knowledge of 82% of the participants was reported as good (Angosta & Speck 2014). Some other studies have revealed similar results (Wagner et al 2005;Baldwin 2014) .…”
Section: Discussionmentioning
confidence: 54%
“…A health-promoting lifestyle mean score in people with a history of hypertension, cholesterol, heart disease, cigarette smoking, and alcohol consumption was not significantly different from those without these risk factors (Mousavian 2014). Another study indicated a significant relationship between type 2 diabetes mellitus and a health-promoting lifestyle (Angosta & Speck 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(12) Toplumun kardiyovasküler hastalıklar risk faktörlerine yönelik bilgi düzeylerinin incelendiği çalışmalarda ise, katılımcıların orta (29,(31)(32)(33) ya da iyi düzeyde bilgiye sahip oldukları belirlenmiştir. (34) Çalışma bulgusu, bireylerin kardiyovasküler hastalıkların önlenmesinde ve tedavisinde kısmen bilgi sahibi olduklarını göstermesi açısından olumlu olarak değerlendirilmektedir. Bu bulgu, kardiyovasküler hastalıklardan korunmak için bireylerin sağlıklı yaşam biçimi davranışlarını benimsemesi ve uygulaması noktasında yarar sağlayabilir.…”
Section: Verilerin Değerlendirilmesiunclassified